Impact of COVID-19 on the Employees of Hotel Industry - Shrestha, Richan; Bhattarai, Prakash C; Shrestha, Bijay; Dhungana, Ganesh (Journal of Tourism & Adventure, 2023)
Travel and mobility restrictions to contain COVID-19 forced many hotels to shut down their business completely or partially. As a result, the hotel sector was hit hard financially. Consequently, majority of the employees of the sector lost their job or were employed with reduced work hours. It affected their financial and psychological aspects. However, there are limited studies focusing on financial and psychological aspects of closures and employment reduction by COVID-19. Therefore, this paper aims to investigate effect of COVID-19 on hotel employees in Kathmandu, Nepal with a survey among the representative sample of 92 hotel industry employees by using a self-constructed questionnaire. The data were then analyzed using descriptive statistics, t-tests, and ANOVA. The result shows that COVID-19 caused a high degree of financial and psychological crises for the employees. Therefore, in conclusion, hotels should create emergency funds to prepare for future crises and provide training and counseling for employees to ensure the employees’ well-being during times of crisis. Similarly, this study recommends hotel employees to save money for emergency situations. The findings of this study are only based on descriptive statistics and future researchers can implement advanced statistical tools and mixed methods to get the in-depth idea of impact of COVID-19 on hotel employees.